Rumen microbial protein supply as estimated from purine derivative excretion on sheep receiving faba beans (vicia faba) as supplement delivered at different feeding frequencies - Natsir, Asmuddin (Indonesian Animal Sciences Society, 2008)
Rapid and extensive degradation of faba beans (Vicia faba) by ruminal microbes can result in substantial and undesirable N loss from the rumen. The purpose of this study was to test the hypothesis that offering faba beans as a supplement more than once a day to sheep receiving a combination of oaten chaff and lucerne chaff as a basal diet will increase microbial protein supply to the intestines. The experiment was conducted in a Latin square design (4 x 4) using four mature merino sheep. The treatments were: T0 = basal diet ad libitum + nil supplements, T1 = T0 + faba beans (FB) fed once daily, T2 = T0 + FB fed twice daily, T3 = T0 + FB fed 8 times daily. The basal diet was given once per day at 09:00 in the morning while FB were given at the rate of approximately 0.5% of live body weight and delivered according to the treatment protocol. Urinary excretion of purine derivative (PD) was used to estimate microbial protein supply. The results indicated that even though treatment statistically had no effects on total urine output, PD excretion in the urine, PD absorbed, estimated microbial N supply, and the efficiency of rumen microbial protein synthesis, provision of supplement to sheep numerically improved microbial N supply by 92% compared to that of control group. However, there were no differences within the supplemented group. Therefore, it is concluded that feeding faba beans more than once a day was unnecessary. Key Words: Purine Derivatives, Microbial Protein Synthesis, Sheep